Hypoxia in myocardial infarction and natriuretic peptides - Arjamaa, Olli (BMJ, 2025)
Background
Mechanical stress on the heart is commonly considered the sole stimulus explaining the synthesis and release of circulating natriuretic peptides and their derivatives. While one of the most critical paradigms in cardiology is that mechanical load increases oxygen consumption, clinical studies on these peptides have neglected the relationship between mechanical stress and oxygen metabolism. At the cellular level, cardiac myocytes have a ubiquitous oxygen-sensing pathway mediated by a nuclear transcription factor, the hypoxia-inducible factor (HIF). Published studies indicate that the human myocardium starts expressing HIF during infarction. In myocardial cell cultures, natriuretic peptides are synthesised and released under hypoxic conditions through immediate and sufficient actions of HIF.
Conclusion
Myocardial oxygen metabolism directly regulates the plasma levels of natriuretic peptides in heart diseases. The function of oxygen gradients should be correlated with circulating natriuretic peptides to achieve better sensitivity in plasma measurements of natriuretic peptides in myocardial infarction.